Mastery of Short Story Writing Skills through Image Series Using Google Forms in Elementary Schools - Habibah, Fitriah Ahmadiyah; Cahyani, Isah (International Conference on Elementary Education, 2021)
Writing is a communication activity to convey messages or information in writing from one party to another. One example of writing skills is writing short stories or short stories which are works of fiction or imaginative fiction by revealing a problem that is written briefly and densely. In the implementation of learning during the current pandemic, learning cannot be carried out directly or face-to-face but with distance learning or so-called e-learning, many applications can be used and support this distance learning, one of which is google form which will be used in research this time. This research was conducted in grade IV in elementary schools. The sample in this study amounted to 40 students. The research design used is descriptive qualitative. The results of this study indicate that students' mastery of writing short story skills using picture series media can be carried out well and get good learning outcomes.